Rome / Helen Gillman, Stefano Cavedoni, Sall Webb - Gillman, Helen
This is the 1st edition of LP's Rome city guide. It incorporates material writtn by Helen Gillman for 3rd edition of the Italy guide.It have Shopping, Excursions chapters, Rome walks chapters, Places to eat, entertainment.. for visitor.